Solar cell, manufacturing method thereof and photovoltaic module
By setting discretely distributed organic adhesive points between the metal layer of the solar cell and the conductive body, the problem of poor gate line reliability in the prior art is solved, higher binding force and thermal expansion resistance are achieved, and the overall reliability of the solar cell is improved.
Patent Information
- Application Number
- CN202411877171.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the solar cell grid lines produced by electroplating technology have poor reliability and are prone to fall off when heated or stressed.
Several discretely distributed organic adhesive dots are provided between the metal layer and the conductive body. The C element of the organic adhesive dots detected by the EDS energy spectrum surface scanning accounts for 1 to 10 wt.% of the total detected element amount to improve the binding force of the gate line and the resistance to thermal expansion.
By distributing organic adhesive spots between the metal layer and the conductive body, the stress at the interface between the conductive body and the metal layer is reduced, the risk of cracking and falling off due to excessive stress is reduced, and the reliability of solar cells is improved.
Smart Images

Figure CN119730475A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of photovoltaic technology, and in particular to a solar cell and a manufacturing method thereof, and a photovoltaic module. Background Art
[0002] The battery grid line is a key part of the solar cell module, and its function is to collect and transmit current. In the related art, the grid line is made on the transparent conductive layer of the battery substrate through an electroplating process. Specifically, a metal layer (i.e., as a seed layer) is first deposited on the battery substrate, and then a conductive body is made on the metal layer through an electroplating process, and finally the conductive body and the metal layer together constitute the metal grid line. However, the inventors have found that the grid lines made by the electroplating process in the related art have poor reliability and are prone to falling off when heated or stressed. Summary of the invention
[0003] The purpose of the present application includes providing a solar cell and a manufacturing method thereof and a photovoltaic module, wherein the reliability of the grid lines is better and the problem of grid line falling off is not likely to occur.
[0004] The embodiments of the present application can be implemented as follows: In a first aspect, the present application provides a solar cell, comprising a cell substrate and a grid line arranged on the surface of the cell substrate, wherein the grid line comprises a metal layer arranged on the surface of the cell substrate and a conductive body arranged on the metal layer, and a plurality of discretely distributed organic glue dots are arranged between the metal layer and the conductive body; the energy signal quantity of the K-edge X-ray of the C element of the organic glue dots in the EDS energy spectrum surface scan is 0.5~5cps / μm 2 , or, the C element of the organic glue spots detected by EDS energy spectrum surface scanning accounts for 1~10wt.% of the total detected elements; wherein, the detection area of the EDS energy spectrum surface scanning is: the area on the surface of the battery substrate corresponding to the gate line after the metal layer and the conductive body of the gate line are corroded and removed and the organic glue spots are left on the surface of the battery substrate.
[0005] In an optional embodiment, the size of the organic glue dots in the thickness direction of the solar cell is 0.005-3 μm.
[0006] In an optional embodiment, the contact area between a single organic glue dot and the metal layer is 0.001-2 μm 2 .
[0007] In an optional implementation manner, the distribution area of the organic glue dots accounts for 0.001% to 10% of the overlapping area of the gate line conductive body and the metal layer.
[0008] In an optional embodiment, in the overlapping area of the conductive body and the metal layer, the distribution density of the organic glue dots is 1 to 100 dots / μm. 2 .
[0009] In an alternative embodiment, the metal layer is a metal seed layer.
[0010] In an optional implementation, the thickness of the metal layer is 50-250 nm, and the thickness of the gate line is 5-20 μm.
[0011] In an optional embodiment, the material of the organic glue dots is selected from at least one of thermosetting resin, thermoplastic resin, rubber and elastomer.
[0012] In an optional embodiment, the thermosetting resin includes at least one of epoxy resin, phenolic resin, unsaturated polyester resin, polyurethane resin, silicone resin and polyimide resin; the thermoplastic resin includes at least one of polyethylene resin, polypropylene resin, polyvinyl chloride resin, polystyrene resin and acrylic resin; the rubber includes at least one of chloroprene rubber, butyl nitrile ethylene propylene rubber, fluororubber and polyisobutylene rubber; and the elastomer includes polyurethane elastomer.
[0013] In an optional embodiment, the metal layer and the conductive body are both made of copper.
[0014] In a second aspect, an embodiment of the present application provides a method for manufacturing a solar cell, comprising: forming a metal seed layer on a battery substrate; Applying a first photosensitive adhesive on the battery substrate to cover the metal seed layer, wherein the first photosensitive adhesive comprises a photosensitive material and an organic adhesive; Exposing and developing the first photosensitive resin to remove the photosensitive material in the first photosensitive resin, so that the organic adhesive forms discretely distributed organic glue dots on the metal seed layer, and the organic glue dots are at least distributed in the grid line area where the grid line is to be formed; The gate lines are formed in the gate line area by an electroplating process.
[0015] In an optional embodiment, the step of exposing and developing the first photosensitive resin to remove the photosensitive material in the first photosensitive resin includes: Exposing the first photosensitive resin in the grid line area; Using a first alkaline solution to remove the first photosensitive resin outside the grid line area; The second alkaline solution is used to remove the photosensitive material in the first photosensitive glue in the grid line area, so that the organic adhesive forms discretely distributed organic glue dots in the grid line area.
[0016] In an optional embodiment, the first alkaline solution is a weak alkaline solution, and the second alkaline solution is a strong alkaline solution.
[0017] In an optional embodiment, the first alkaline solution is a sodium carbonate solution, and the second alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.
[0018] In an optional implementation, the first photosensitive resin in the grid line area is exposed by a laser printing process.
[0019] In an alternative embodiment, the organic adhesive is selected from at least one of a thermosetting resin, a thermoplastic resin, a rubber, and an elastomer.
[0020] In an optional embodiment, the thermosetting resin includes at least one of epoxy resin, phenolic resin, unsaturated polyester resin, polyurethane resin, silicone resin and polyimide resin; the thermoplastic resin includes at least one of polyethylene resin, polypropylene resin, polyvinyl chloride resin, polystyrene resin and acrylic resin; the rubber includes at least one of chloroprene rubber, butyl nitrile ethylene propylene rubber, fluororubber and polyisobutylene rubber; and the elastomer includes polyurethane elastomer.
[0021] In an optional implementation, the mass proportion of the organic adhesive in the first photosensitive adhesive is 0.001% to 10.0%.
[0022] In an optional embodiment, the viscosity of the organic adhesive is 1000-5000 mPa·s.
[0023] In an optional implementation, the thickness of the first photosensitive resin is 0.5-3 μm.
[0024] In an optional embodiment, the step of forming the gate line in the gate line area by an electroplating process includes: coating a second photosensitive adhesive on the battery substrate to cover the metal seed layer; The second photosensitive resin in the grid line area is removed by exposure and development; Placing the battery substrate in an electroplating solution for electroplating to form grid lines in the grid line area; Using a third alkaline solution to remove the second photosensitive resin outside the grid line area; An acid solution is used to remove the metal seed layer outside the gate line area.
[0025] In an optional embodiment, after the step of forming the grid lines in the grid line region by electroplating, the method for forming a solar cell further comprises: The cell substrate with grid lines is subjected to light injection treatment.
[0026] In an optional implementation, the light injection temperature of the light injection treatment is 200-220° C., and the light injection time is 60-120 s.
[0027] In a third aspect, an embodiment of the present application provides a photovoltaic module, comprising a solar cell according to any one of the first aspects above, or a solar cell manufactured by the method for manufacturing a solar cell according to any one of the second aspects above.
[0028] The beneficial effects of the embodiments of the present application include: The solar cell provided in the embodiment of the present application includes a cell substrate and a grid line arranged on the surface of the cell substrate, the grid line includes a metal layer arranged on the surface of the cell substrate and a conductive body arranged on the metal layer, and a plurality of discretely distributed organic glue dots are arranged between the metal layer and the conductive body; the energy signal quantity of the K-edge X-ray of the C element of the organic glue dots in the EDS energy spectrum surface scan is 0.5~5cps / μm 2 , or, the C element of the organic glue point detected by the EDS energy spectrum scan accounts for 1~10wt.% of the total detected elements; wherein, the detection area of the EDS energy spectrum scan is: after the metal layer and the conductive body of the grid line are corroded and removed and the organic glue point is left on the surface of the battery substrate, the area on the surface of the battery substrate corresponding to the grid line. The metal layer is tightly combined with the battery substrate, and it is not easy to fall off, and it can deform with the thermal expansion of the battery substrate. By distributing a certain density of organic glue points between the metal layer and the conductive body, the organic glue points have a lower hardness than the grid line, so that when the solar cell is heated, the organic glue points can provide space for the battery substrate and the conductive body to expand through a certain degree of deformation. Since the organic glue points can absorb the thermal deformation of the battery substrate and the conductive body, the stress at the interface between the conductive body and the metal layer can be reduced, thereby reducing the risk of cracking and falling off due to excessive stress. In addition, the organic glue points themselves have viscosity, which can tightly adhere the conductive body to the metal layer and increase the interface bonding force between the conductive body and the metal layer. Therefore, the solar cell provided in the embodiment of the present application is not prone to the problem of the conductive body falling off and has better reliability.
[0029] The method for manufacturing a solar cell provided in the embodiment of the present application is used to manufacture the above-mentioned solar cell. The photovoltaic module provided in the embodiment of the present application includes the above-mentioned solar cell or the solar cell manufactured by the above-mentioned manufacturing method, so it has better reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 A schematic diagram of a solar cell in one embodiment of the present application; Figure 2 This is a flow chart of a method for manufacturing a solar cell in one embodiment of the present application; Figure 3 This is a first scanning electron microscope image of an organic glue dot on a yellow film in an embodiment of the present application; Figure 4 A second scanning electron microscope image of an organic glue dot on a yellow film in an embodiment of the present application; Figure 5 A schematic diagram of test points for a shear resistance test of a gate line in one embodiment of the present application; Figure 6 This is a cross-sectional view of a solar cell in one embodiment of the present application.
[0032] Icon: 100 - battery substrate; 110 - silicon wafer; 120 - first intrinsic amorphous silicon layer; 130 - second intrinsic amorphous silicon layer; 140 - n-type doped layer; 150 - p-type doped layer; 160 - first transparent conductive layer; 170 - second transparent conductive layer; 200 - gate line; 210 - metal layer; 220 - conductive body. DETAILED DESCRIPTION
[0033] In the related technology of making grid lines by electroplating process, a metal layer (i.e., as a seed layer) is first deposited on the battery substrate, and then a conductive body is made on the metal layer by electroplating process. Finally, the conductive body and the metal layer together constitute the metal grid line 200. The inventor found that the metal layer of the grid line is thin and has good bonding with the battery substrate. Even when the battery substrate expands or contracts, the metal layer can still maintain a close fit with the battery substrate and shrink adaptively with the expansion of the battery substrate. However, the thermal expansion coefficients of the conductive body and the battery substrate are quite different. Taking the copper grid line as an example, its thermal expansion coefficient is 15×10 -6 / ℃~17×10 -6 / ℃, the thermal expansion coefficient of silicon wafer, the main material of the battery matrix, is 2.5×10 -6 / ℃~3.5×10 -6 / ℃, so there will be a thermal mismatch problem between the battery matrix and the conductive body. When the solar cell is heated, the metal layer expands with the battery matrix, which is inconsistent with the expansion of the conductive body, causing a large stress at the interface between the metal layer and the conductive body, causing the conductive body to easily fall off from the metal layer when heated (cold). In the production process of solar cells and photovoltaic modules, there will be electrical injection or light injection processes, as well as film curing and cross-linking heating processes. All thermal processes will cause internal stress in the grid line. The greater the difference in thermal expansion coefficient between the conductive body and the battery matrix, the greater the stress at the interface between the conductive body and the metal layer, and then the grid line will fall off. In addition, the battery matrix and some grid lines themselves have high hardness and poor flexibility (the hardness of silicon wafers can reach 6~7Mohs, and the hardness of copper grid lines can reach 2.5~3.0Mohs). In the process of solar cell manufacturing, when the grid line is rubbed or other objects touch the grid line, it is easy to break the grid line from the battery matrix, and the pyramid structure on the surface of the battery matrix is broken, resulting in the problem of missing or broken grid lines. It can be seen that the reliability of the grid lines of solar cells in the related art is relatively poor.
[0034] To this end, the embodiment of the present application provides a solar cell and a method for manufacturing the same, by adding discretely distributed organic glue dots between the metal layer and the conductive body, thereby improving the reliability of the grid line. In addition, the embodiment of the present application also provides a photovoltaic module, including the above-mentioned solar cell. It should be noted that the "organic glue dots" mentioned in this application all refer to organic bodies with viscosity and elasticity.
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0036] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0037] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0038] In the description of the present application, it should be noted that if the terms "upper", "lower", "inside", "outside", etc. appear to indicate an orientation or position relationship, it is based on the orientation or position relationship shown in the drawings, or is the orientation or position relationship in which the product of the invention is usually placed when used. It is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.
[0039] In addition, the terms “first”, “second”, etc., if used, are merely used to distinguish between the descriptions and should not be understood as indicating or implying relative importance.
[0040] It should be noted that, in the absence of conflict, the features in the embodiments of the present application may be combined with each other.
[0041] Figure 1 This is a schematic diagram of a solar cell in an embodiment of the present application. Please refer to Figure 1 The solar cell provided in this embodiment includes a cell substrate 100 and a gate line 200 arranged on the cell substrate 100. In this embodiment, the solar cell is introduced as a silicon heterojunction cell as an example, and the cell substrate 100 includes a silicon wafer 110, a first intrinsic amorphous silicon layer 120, a second intrinsic amorphous silicon layer 130, an n-type doped layer 140, a p-type doped layer 150, a first transparent conductive layer 160 and a second transparent conductive layer 170. Among them, the first intrinsic amorphous silicon layer 120, the n-type doped layer 140 and the first transparent conductive layer 160 are sequentially stacked and arranged on one side of the silicon wafer 110 (usually the light-receiving side, that is, the front side), and the second intrinsic amorphous silicon layer 130, the p-type doped layer 150 and the second transparent conductive layer 170 are sequentially stacked and arranged on the other side of the silicon wafer 110 (usually the backlight side, that is, the back side). Optionally, the silicon wafer 110 is n-type doped single crystal silicon. The n-type doping layer 140 and the p-type doping layer 150 may be amorphous silicon or microcrystalline silicon. Optionally, the doping element of the n-type doping layer 140 is phosphorus, and the doping element of the p-type doping layer 150 is boron.
[0042] Optionally, the thickness of the silicon wafer 110 is 1-10 μm, the thickness of the first intrinsic amorphous silicon layer 120 is 3-10 nm, the thickness of the second intrinsic amorphous silicon layer 130 is 3-14 nm, and the thickness of the n-type doped layer 140 and the p-type doped layer 150 are both 5-30 nm. The material of the first transparent conductive layer 160 and the second transparent conductive layer 170 can be indium tin oxide (ITO), and the thickness is 90-110 nm. The gate line 200 is specifically arranged on the first transparent conductive layer 160 and the second transparent conductive layer 170. Optionally, the thickness of the metal layer 210 is 50-250 nm, and the overall thickness of the gate line 200 is 5-20 μm. It should be understood that the thickness of each of the above structures refers to its size in the stacking direction of each film layer of the battery substrate 100.
[0043] In other optional embodiments, the solar cell may also be other types of cells, such as perovskite cells and tunnel oxide passivation contact cells (TOPCon). The specific structures of the cell substrates of different types of solar cells are different and can be adaptively adjusted according to the existing technology, which will not be described here one by one.
[0044] In an embodiment of the present application, the gate line 200 includes a metal layer 210 disposed on the surface of the battery substrate 100 and a conductive body 220 disposed on the metal layer 210. Optionally, the metal layer 210 and the conductive body 220 are made of the same material, such as copper. In other embodiments, the metal layer 210 and the conductive body 220 can also be made of other metals such as gold, silver, aluminum, nickel, and molybdenum. In the present embodiment, the metal layer 210 is a metal seed layer, which is first formed on the surface of the battery substrate 100 by a physical vapor deposition process before the gate line 200 is formed by electroplating. In the embodiment of the present application, a plurality of discretely distributed organic glue dots ( Figure 1 (not shown in the figure). The organic glue dots have a lower hardness relative to the grid lines 200, so that when the solar cell is heated, the organic glue dots can provide a space for the battery matrix 100 and the conductive body 220 to expand through a certain degree of deformation, thereby reducing the risk of cracking due to excessive stress at the interface between the metal layer 210 and the conductive body 220. In addition, the organic glue dots themselves have viscosity, which can tightly adhere the conductive body 220 to the metal layer 210, and increase the interface bonding force between the conductive body 220 and the metal layer 210. And the organic glue dots have better flexibility relative to the grid lines 200, and it is not easy for the organic glue dots and the metal layer 210 or the conductive body 220 to fall off due to large stress (such as shear stress). Therefore, the solar cell provided in the embodiment of the present application has better reliability and is not prone to problems of grid detachment and grid breakage.
[0045] In an embodiment of the present application, the amount of organic glue dots between the metal layer 210 and the conductive body 220 can be measured using the number of energy signals of the K-edge X-rays in the EDS energy spectrum scan. EDS energy spectrum is specifically Energy-Dispersive X-ray Spectroscopy (EDS), which is a material characterization technology used to determine the types and spatial distribution of elements in a sample. The principle of EDS energy spectrum scan is based on the generation and detection of X-rays, and is achieved through an EDS detector in a scanning electron microscope (Scanning Electron Microscope, SEM) or a transmission electron microscope (Transmission Electron Microscope, TEM). In SEM or TEM, a high-energy electron beam bombards the surface of the sample, causing the inner electrons of the atoms in the sample to be excited or removed to form holes. High-energy-level electrons transition to low-energy-level holes, releasing characteristic X-rays. The energy of these characteristic X-rays is related to the atomic number of the element, and each element has a unique characteristic X-ray energy. As for the carbon element, its characteristic X-ray is generated by the K-layer electron transition of the carbon atom. Therefore, in the EDS energy spectrum surface scan, the amount of carbon element can be characterized by the amount of energy signal of the K-edge X-ray of the carbon element. In this embodiment, in the overlapping area of the conductive body 220 and the metal layer 210, the amount of energy signal of the K-edge X-ray of the carbon element of the organic glue point in the EDS energy spectrum surface scan can be used to characterize the amount of organic glue points between the conductive body 220 and the metal layer 210. The larger the amount of energy signal of the K-edge X-ray, the larger the amount of organic glue points, and the smaller the amount of energy signal of the K-edge X-ray, the smaller the amount of organic glue points.
[0046] In the embodiment of the present application, the energy signal quantity of the K-edge X-ray of the C element of the organic glue dot in the EDS energy spectrum scan (hereinafter referred to as the K-edge signal quantity) is 0.5~5cps / μm 2 The data is the EDS energy spectrum scan data collected at a voltage of 15kV. The K-edge signal of the carbon element is calculated by integration (usually there is a signal peak at 284eV. Different equipment calibrations will cause a certain offset in the peak position, which will not affect the identification and definition of the peak) and divided by the acquisition area and acquisition time, and the K-edge signal of the carbon element per unit area per unit time is obtained, and the unit is cps / μm 2 .
[0047] It is understood that the organic glue dots between the metal layer 210 and the conductive body 220 should not be too many or too few. When the distribution of the organic glue dots is less than 0.5 cps / μm 2When the organic glue dots are more sparsely distributed, the stress on each glue dot will be greater. Too few organic glue dots cannot provide sufficient bonding and buffering effects, so it is difficult to prevent debonding or breakage caused by local stress concentration, and thus the bonding strength between the conductive body 220 and the metal layer 210 cannot be improved. When the distribution of organic glue dots is more than 5.0 cps / μm 2 Although increasing the density of organic glue dots can improve the bonding reliability, too high a density of organic glue dots will affect the contact between the conductive body 220 and the metal layer 210, resulting in an increase in the contact resistance between the conductive body 220 and the metal layer 210, which will reduce the fill factor of the solar cell and the cell efficiency.
[0048] In other optional embodiments, in addition to using the K-edge signal to characterize the amount of organic glue dots, the amount of organic glue dots may also be characterized by the ratio of the amount of C element detected in the overlapping area of the conductive body 220 and the metal layer 210 to the total amount of detected elements. Optionally, the C element of the organic glue dots detected by the EDS energy spectrum scan accounts for 1-10wt.% of the total amount of detected elements.
[0049] In the above-mentioned method of using the K-edge signal amount or the mass proportion of the C element to characterize the amount of organic glue dots, the detection area of the EDS energy spectrum surface scan is: after the metal layer 210 and the conductive body 220 of the gate line 200 are corroded and removed and the organic glue dots are left on the surface of the battery matrix 100, the area on the surface of the battery matrix 100 corresponding to the gate line 200. In other words, before performing the above-mentioned EDS energy spectrum surface scan, the metal layer 210 and the conductive body 220 can be removed first, so that the organic glue dots are settled in the area corresponding to the gate line 200 on the surface of the battery matrix 100, and then the EDS energy spectrum surface scan is performed on the area. Optionally, the gate line 200 is soaked in an etching solution containing sulfuric acid and hydrogen peroxide until the conductive body 220 and the metal layer 210 are removed by reaction, and the battery matrix 100 is leaked, and then the area on the surface of the battery matrix 100 corresponding to the gate line 200 is detected by EDS energy spectrum surface scan, and the C element therein is detected (for example, the K-edge signal amount of the C element is obtained or the amount of the C element is detected The proportion of the total element amount detected).
[0050] When using EDS energy spectrum scanning to detect the element content, the conductive body 220 and the metal layer 210 are first separated, and then the surface of the metal layer 210 (the surface bonded to the conductive body 220 ) is subjected to EDS energy spectrum scanning.
[0051] Optionally, in the overlapping area of the conductive body 220 and the metal layer 210 in this embodiment, the distribution density of the organic glue dots is 1-100 dots / μm. 2 .
[0052] Optionally, the amount of organic glue dots can also be characterized by the ratio of the distribution area of the organic glue dots to the overlapping area of the conductive body 220 and the metal layer 210. In this embodiment, the distribution area of the organic glue dots accounts for 0.001% to 10% of the overlapping area of the conductive body 220 and the metal layer 210.
[0053] Optionally, the size of the organic glue dots in the thickness direction of the solar cell is 0.005-3 μm. It is understandable that if the thickness of the organic glue dots is too thin, it is easy to cause the organic glue dots to have insufficient ability to absorb the deformation of the gate line 200, that is, it is difficult to effectively alleviate the stress problem and it is difficult to improve the gate detachment and gate breakage problems. However, if the organic glue dots are too thick, the contact resistance between the conductive body 220 and the metal layer 210 will increase, and the conductivity of the gate line 200 will deteriorate.
[0054] Optionally, the contact area between a single organic glue dot and the metal layer 210 is 0.001-2 μm 2 If the contact area between a single organic glue dot and the metal layer 210 is too small, it is easy to cause the organic glue dot to be insufficient in absorbing the deformation of the gate line 200, that is, it is difficult to effectively alleviate the stress problem and to improve the gate detachment and gate breakage problems. If the contact area is too large, the contact resistance between the conductive body 220 and the metal layer 210 will increase, and the conductivity of the gate line 200 will deteriorate.
[0055] Optionally, the material of the organic glue dots is selected from at least one of thermosetting resins, thermoplastic resins, rubbers and elastomers. Among them, the thermosetting resin includes at least one of epoxy resins, phenolic resins, unsaturated polyester resins, polyurethane resins, silicone resins and polyimide resins; the thermoplastic resin includes at least one of polyethylene resins, polypropylene resins, polyvinyl chloride resins, polystyrene resins and acrylic resins; the rubber includes at least one of chloroprene rubber, butyl nitrile ethylene propylene rubber, fluororubber and polyisobutylene rubber; the elastomer includes polyurethane elastomer. It should be understood that the material of the organic glue dots is not limited to the materials listed above, and other organic materials that can play a buffering and bonding role can be used as the material of the organic glue dots in the embodiments of the present application.
[0056] Figure 2 Flow chart of a method for manufacturing a solar cell in one embodiment of the present application. The method for manufacturing a solar cell provided in the embodiment of the present application can be used to manufacture the solar cell provided in the above embodiment. Figure 2 As shown, the method for manufacturing a solar cell according to an embodiment of the present application comprises the following steps: Step S100 , forming a metal seed layer on the battery substrate 100 .
[0057] In the embodiment of the present application, a battery substrate 100 may be first obtained, and then a metal seed layer may be deposited on the surface of the battery substrate 100 using a physical vapor deposition process (such as magnetron sputtering).
[0058] To produce Figure 1 Taking the solar cell shown as an example, the silicon wafer 110 can be textured first to form a positive pyramid texture surface. The first intrinsic amorphous silicon layer 120, the second intrinsic amorphous silicon layer 130, the n-type doping layer 140 and the p-type doping layer 150 are deposited on the silicon wafer 110 by plasma enhanced chemical vapor deposition (PECVD). Then, at least one of the magnetron sputtering process, the rapid plasma deposition process or the atomic layer deposition process is used to deposit the first transparent conductive layer 160 and the second transparent conductive layer 170, thereby obtaining the battery substrate 100. In this embodiment, the method for manufacturing the battery substrate 100 is introduced by taking the manufacture of a silicon heterojunction battery as an example. In other embodiments, the method for manufacturing the battery substrate 100 can be designed according to the type of solar cell actually manufactured.
[0059] After the battery substrate 100 is manufactured, a metal seed layer (such as a copper seed layer) can be deposited on the surface of the first transparent conductive layer 160 and the second transparent conductive layer 170 using a PVD magnetron sputtering device. The thickness of the metal seed layer can be selected to be 50-250 nm. The manufactured battery substrate 100 covered with a metal seed layer is usually called a "yellow film".
[0060] Furthermore, after the metal seed layer is made, the four edges and corners of the yellow film can be wrapped with edge glue to protect the side of the yellow film in subsequent processes. The width of the edge glue is 300-700 μm, and the thickness of the edge glue is 10-15 μm.
[0061] Step S200: coating a first photosensitive adhesive on the battery substrate 100 to cover the metal seed layer. The first photosensitive adhesive includes a photosensitive material and an organic adhesive.
[0062] In the embodiment of the present application, the photosensitive material will be denatured due to exposure to light, thereby distinguishing it from the non-photosensitive area. For example, some specific developers can only remove the undenatured photosensitive material, but cannot remove the denatured photosensitive material. In the embodiment of the present application, the organic adhesive is used as the raw material for the subsequent formation of organic glue dots, and is applied to the metal seed layer together with the photosensitive material. Optionally, the thickness of the first photosensitive glue is 0.5~3.0μm.
[0063] Optionally, the organic adhesive is selected from at least one of a thermosetting resin, a thermoplastic resin, a rubber and an elastomer. Optionally, the thermosetting resin includes at least one of an epoxy resin, a phenolic resin, an unsaturated polyester resin, a polyurethane resin, a silicone resin and a polyimide resin; the thermoplastic resin includes at least one of a polyethylene resin, a polypropylene resin, a polyvinyl chloride resin, a polystyrene resin and an acrylic resin; the rubber includes at least one of chloroprene rubber, butyl nitrile ethylene propylene rubber, fluororubber and polyisobutylene rubber; and the elastomer includes a polyurethane elastomer.
[0064] Optionally, the mass proportion of the organic adhesive in the first photosensitive adhesive is 0.001% to 10.0%. It is understandable that too little organic adhesive cannot form a sufficient amount of organic adhesive dots (for example, the mass proportion of the organic adhesive is less than 0.001%), and it is difficult to ensure that the structural reliability of the gate line 200 is improved. Adding too much organic adhesive (for example, the mass proportion of the organic adhesive is greater than 10.0%) will make the organic adhesive dots too dense. For the electroplating process, the conductive body 220 starts to grow from the metal layer 210. Too dense organic adhesive dots will restrict the growth of the conductive body 220, resulting in a large number of holes inside the gate line 200, and will also cause irregular (overflow plating, dendrite) growth of the gate line 200, thereby affecting the conductive performance and structural stability. By controlling the mass ratio of the organic adhesive in the first photosensitive resin, the amount of organic adhesive dots in the final gate line 200 can be effectively controlled, so that it can effectively play a buffering role, improve the bonding between the metal layer 210 and the conductive body 220, and at the same time ensure that the conductivity of the gate line 200 will not deteriorate.
[0065] Optionally, the viscosity of the organic adhesive is 1000-5000 mPa·s. By controlling the viscosity of the organic adhesive within a reasonable range, the final organic glue dots can be well dispersed.
[0066] Step S300, exposing and developing the first photosensitive resin to remove the photosensitive material in the first photosensitive resin, so that the organic adhesive forms discretely distributed organic glue dots on the metal seed layer, and the organic glue dots are distributed at least in the gate line area where the gate line 200 is to be formed.
[0067] In the embodiment of the present application, after the photosensitive material in the first photosensitive resin is removed, discretely distributed granular organic glue dots remain on the metal seed layer. The organic glue dots should be distributed at least in the grid line area where the grid line 200 is to be formed, so as to ensure that the grid line 200 obtained in the subsequent production has discretely distributed organic glue dots.
[0068] Optionally, step S300 specifically includes: Step S310, exposing the first photosensitive resin in the gate line area; Step S320, using a first alkaline solution to remove the first photosensitive resin outside the gate line area; Step S330: using a second alkaline solution to remove the photosensitive material in the first photosensitive adhesive in the gate line region, so that the organic adhesive forms discretely distributed organic adhesive dots in the gate line region.
[0069] Optionally, in this embodiment, a laser printing process is used to expose the first photosensitive resin in the gate line area.
[0070] In the present embodiment, the first photosensitive glue in the grid line area is exposed so that the photosensitive material therein undergoes a cross-linking reaction, so it can prevent the photosensitive material from reacting with the first alkaline solution. In addition, after the photosensitive material in the grid line area undergoes a cross-linking reaction, the cross-linking reaction will also affect the organic adhesive in the photosensitive material, causing the organic adhesive to adhere more firmly to the surface of the metal seed layer, and avoid being dissolved and washed away by the second alkaline solution in step S330. Therefore, the first alkaline solution can remove the first photosensitive glue outside the grid line area (i.e., the undenatured photosensitive material and the organic adhesive therein). The second alkaline solution is different from the first alkaline solution, and it can remove the photosensitive material in the first photosensitive glue in the grid line area (i.e., the photosensitive material after denaturation), and finally only retain at least part of the organic adhesive in the grid line area, and this part of the organic adhesive forms discretely distributed organic glue dots in the grid line area.
[0071] Optionally, the first alkaline solution is a weak alkaline solution, and the second alkaline solution is a strong alkaline solution.
[0072] Optionally, the first alkaline solution is a sodium carbonate solution, wherein the sodium carbonate concentration is 10-20 g / L, the temperature of the first alkaline solution is 25-35° C., the pressure of the nozzle is 0.5-2.5 bar, and the pH value of the first alkaline solution is 8-13. Optionally, the second alkaline solution is a potassium hydroxide solution or a sodium hydroxide solution, and the second alkaline solution can not only remove the photosensitive material in the first photosensitive glue in the grid line area, but also remove the edge glue.
[0073] Figure 3 This is a first scanning electron microscope image of an organic glue dot on a yellow film in an embodiment of the present application; Figure 4 This is a second SEM image of an organic glue dot on a yellow film in one embodiment of the present application. Figure 3 and Figure 4 As shown, in this embodiment, the battery substrate 100 has a velvet surface, and the velvet surface is a pyramid structure. The metal seed layer covers the surface of the battery substrate 100, and the organic glue dots are distributed on the metal seed layer.
[0074] Step S400 , manufacturing the gate line 200 in the gate line region by electroplating process.
[0075] Optionally, step S400 specifically includes: Step S410, coating a second photosensitive adhesive on the battery substrate 100 to cover the metal seed layer; Step S420, removing the second photosensitive resin in the gate line area by exposure and development; Step S430, placing the battery substrate 100 in a plating solution for electroplating to form a gate line 200 in the gate line area; Step S440, using a third alkaline solution to remove the second photosensitive resin outside the gate line area; Step S450: using an acid solution to remove the metal seed layer outside the gate line region.
[0076] In this embodiment, steps S410 and S420 can make the non-gridline area in the metal seed layer covered by the second photosensitive glue, while the gridline area is exposed. The exposure step in step S420 can adopt a laser printing process, and the designed gridline 200 pattern is printed on the film layer of the second photosensitive glue by laser, and the exposed area is denatured (non-gridline area is photosensitive), so as to be distinguished from the non-photosensitive area (i.e., the gridline area). In the development process, sodium carbonate solution is used as a developer to clean and remove the second photosensitive glue (not photosensitive) in the gridline area. Optionally, the sodium carbonate concentration is controlled at 10~20g / L, the solution temperature is 25℃~35℃, the nozzle pressure is 0.5bar~2.5bar, and the solution pH range is 8~13. The alkaline developer reacts with the second photosensitive glue that is not photosensitive, so that the second photosensitive glue in the gridline area that is not photosensitive is dissolved, so the gridline area that is not photosensitive will form a development groove.
[0077] Taking the manufacture of copper gate lines as an example, optionally, the electroplating process of step S430 is performed in a copper sulfate electroplating solution, and the height of the gate line 200 is controlled to be 5-20 μm.
[0078] The third alkaline solution in step S440 can be a strong alkaline solution such as sodium hydroxide solution or potassium hydroxide solution. The acid solution in step S450 can be a dilute sulfuric acid solution. After step S450 is performed, only the portion of the metal seed layer that participates in forming the gate line 200 is left. Figure 1 In the embodiment, only the gate line 200 is left on the metal layer 210 , the first transparent conductive layer 160 , and the second transparent conductive layer 170 of the battery substrate 100 .
[0079] Furthermore, after the gate line 200 is manufactured, the method for manufacturing a solar cell according to the embodiment of the present application further includes: performing a light injection process on the cell substrate 100 with the gate line 200 .
[0080] Through the light injection treatment, the adhesion between the organic glue dots and the metal layer 210, and between the organic glue dots and the conductive body 220 can be increased, thereby improving the structural reliability of the grid line 200. Optionally, the light injection temperature is 200°C to 220°C, and the duration is 60s to 120s. After the light injection treatment, the electrical performance test of the solar cell can be performed.
[0081] The method for manufacturing a solar cell is specifically described below through Example 1.
[0082] Embodiment 1: First obtain Figure 1 The battery substrate 100 of the heterojunction battery shown in the figure is then deposited with a copper metal seed layer on the surface of the battery substrate 100 by magnetron sputtering to obtain a yellow film. The thickness of the metal seed layer is 150nm. The four edges and corners of the yellow film are wrapped with edge glue, the width of the edge glue is 500μm, and the thickness of the edge glue is 10μm.
[0083] A 2 μm thick first photosensitive adhesive is coated on the battery substrate 100 to cover the metal seed layer. The first photosensitive adhesive includes 95 wt.% of photosensitive material and 5 wt.% of epoxy resin. The viscosity of the epoxy resin added is 2500 mPa·s. The first photosensitive adhesive in the grid line area is exposed, and a 15 g / L sodium carbonate solution is used to remove the first photosensitive adhesive outside the grid line area. The temperature of the sodium carbonate solution is 25°C, the pressure of the nozzle is 1 bar, and the pH value is 9. Then, a sodium hydroxide solution is used to remove the photosensitive material in the first photosensitive adhesive in the grid line area, so that the epoxy resin forms discretely distributed organic adhesive dots in the grid line area.
[0084] A second photosensitive adhesive is coated on the battery substrate 100 to cover the metal seed layer. The second photosensitive adhesive in the non-gridline area is exposed. The second photosensitive adhesive in the gridline area is removed by using a sodium carbonate solution, wherein the sodium carbonate concentration in the sodium carbonate solution is controlled at 15 g / L, the solution temperature is 25°C, the nozzle pressure is 1 bar, and the solution pH is 9. The battery substrate 100 is placed in a copper sulfate electroplating solution for electroplating to form a copper gridline 200 in the gridline area, and the height of the gridline 200 is 12 μm. Sodium hydroxide solution is used to remove the second photosensitive adhesive outside the gridline area. Then dilute sulfuric acid is used to remove the metal seed layer outside the gridline area. The battery substrate 100 with the gridline 200 is subjected to light injection treatment, the light injection temperature is 200°C, and the duration is 80 seconds, and finally a solar cell is obtained.
[0085] Figure 5 Schematic diagram of test points for the shear resistance test of the gate line 200 in one embodiment of the present application. Figure 5As shown, in this embodiment, the reliability of the grid line 200 of the solar cell is tested. The specific method is to use a thrust meter to apply a thrust to the grid line 200, the thrust direction is perpendicular to the thickness direction of the solar cell sheet (that is, the stacking direction of each film layer in the battery matrix 100), and perpendicular to the length direction of the grid line 200. By applying a thrust to the grid line 200, a shear force can be generated between the grid line 200 and the battery matrix 100. The maximum thrust that the grid line 200 can withstand is used to characterize the anti-shear ability of the grid line 200. Figure 5 As shown, in order to reduce the measurement error, five positions are taken on the solar cell ( Figure 5 The shear resistance test is carried out at the midpoint A, point B, point C, point D, and point E), and the average value of the maximum thrust value that the grid line 200 can withstand at each position is taken to evaluate the shear resistance of the grid line 200 of the solar cell. Table 1 is the shear resistance test results of the solar cells prepared by Example 1 and Comparative Example 1. Among them, the manufacturing method of the solar cell of Comparative Example 1 is completely consistent with the process parameters of Example 1 except that the organic adhesive is not added to the first photosensitive adhesive. Five solar cells are made by the manufacturing methods of Example 1 and Comparative Example 1, and the shear resistance test is carried out.
[0086] Table 1:
[0087] Figure 6 FIG. 1 is a cross-sectional view of a solar cell in one embodiment of the present application. Figure 6 As shown, the conductive body 220 and the metal layer 210 are both light gray, the battery substrate 100 is dark gray, the metal layer 210 is closely attached to the battery substrate 100, and there is an organic glue point between the metal layer 210 and the conductive body 220. The EDS energy spectrum surface scan (under 15kV) of the grid line area shows that the K-edge X-ray energy signal of the C element of the organic glue point is 2 cps / μm 2 The number of organic glue dots in the gate line area is 40 / μm 2 , the number of organic glue spots on the cross section is 7 / μm.
[0088] It can be seen from Table 1 and related test results that, through the manufacturing method provided in the embodiment of the present application, a plurality of discretely distributed organic glue dots can be produced between the metal layer 210 and the conductive body 220, and these organic glue dots can significantly improve the shear resistance of the gate line 200, thereby improving the reliability of the gate line 200.
[0089] It should be understood that the manufacturing method of the solar cell provided in the embodiment of the present application is not limited to the manufacturing method listed in the above embodiment. In other embodiments, the solar cell provided in the embodiment of the present application can also be manufactured by other manufacturing methods.
[0090] The embodiments of the present application also provide a photovoltaic assembly including the solar cell provided in the embodiments of the present application, or including the solar cell manufactured by the manufacturing method provided in the embodiments of the present application.
[0091] In summary, the embodiments of the present application provide a solar cell and a method for manufacturing the same, and a photovoltaic module. The solar cell includes a cell substrate 100 and a grid line 200 disposed on the surface of the cell substrate 100. The grid line 200 includes a metal layer 210 disposed on the surface of the cell substrate 100 and a conductive body 220 disposed on the metal layer 210. A plurality of discretely distributed organic glue dots are disposed between the metal layer 210 and the conductive body 220. The energy signal quantity of the C element of the organic glue dots in the K-edge X-ray in the EDS energy spectrum surface scan is 0.5~5cps / μm. 2 , or, the C element of the organic glue dots detected by the EDS energy spectrum scan accounts for 1-10wt.% of the total detected elements; the detection area of the EDS energy spectrum scan is: after the metal layer 210 and the conductive body 220 of the grid line 200 are corroded and removed and the organic glue dots are left on the surface of the battery substrate 100, the area on the surface of the battery substrate 100 corresponding to the grid line 200. The metal layer 210 is tightly combined with the battery substrate 100, and is not easy to fall off, and can be deformed with the thermal expansion of the battery substrate 100. By distributing a certain density of organic glue dots between the metal layer 210 and the conductive body 220, the organic glue dots have a lower hardness than the grid line 200, so that when the solar cell is heated, the organic glue dots can deform to a certain extent to provide space for the battery substrate 100 and the conductive body 220 to expand. Since the organic glue dots can absorb the thermal deformation of the battery matrix 100 and the conductive body 220, the stress at the interface between the conductive body 220 and the metal layer 210 can be reduced, thereby reducing the risk of cracking and falling off due to excessive stress. In addition, the organic glue dots themselves have viscosity, which can tightly adhere the conductive body 220 to the metal layer 210, and increase the interface bonding force between the conductive body 220 and the metal layer 210. And the organic glue dots have better flexibility relative to the grid line 200, and it is not easy for the organic glue dots and the metal layer 210 or the conductive body 220 to fall off due to large stress (such as shear stress). Therefore, the solar cell provided in the embodiment of the present application is not prone to the problem of the conductive body 220 falling off, and has better reliability.
[0092] The method for manufacturing a solar cell provided in the embodiment of the present application is used to manufacture the above-mentioned solar cell. The photovoltaic module provided in the embodiment of the present application includes the above-mentioned solar cell or the solar cell manufactured by the above-mentioned manufacturing method, so it has better reliability.
[0093] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A solar cell, characterized in that: The invention comprises a battery substrate and a grid line arranged on the surface of the battery substrate, wherein the grid line comprises a metal layer arranged on the surface of the battery substrate and a conductive body arranged on the metal layer, and a plurality of discretely distributed organic glue dots are arranged between the metal layer and the conductive body; the energy signal quantity of the K-edge X-ray of the C element of the organic glue dots in the EDS energy spectrum surface scan at a voltage of 15 kV is 0.5-5 cps / μm 2 , or, the C element of the organic glue dots detected by EDS energy spectrum scanning accounts for 1~10wt.% of the total detected elements; wherein the detection area of the EDS energy spectrum scanning is: after the metal layer and the conductive body of the gate line are corroded and removed and the organic glue dots are left on the surface of the battery substrate, the area of the battery substrate surface corresponding to the gate line.
2. The solar cell according to claim 1, characterized in that The size of the organic glue dots in the thickness direction of the solar cell is 0.005-3 μm.
3. The solar cell according to claim 1, characterized in that The contact area between a single organic glue point and the metal layer is 0.001-2 μm 2 .
4. The solar cell according to claim 1, characterized in that The distribution area of the organic glue dots accounts for 0.001% to 10% of the overlapping area of the gate line conductive body and the metal layer.
5. The solar cell according to claim 1, characterized in that: In the overlapping area between the conductive body and the metal layer, the distribution density of the organic glue dots is 1-100 dots / μm 2 .
6. The solar cell according to claim 1, characterized in that The metal layer is a metal seed layer.
7. The solar cell according to claim 1, characterized in that The thickness of the metal layer is 50-250 nm, and the thickness of the gate line is 5-20 μm.
8. The solar cell according to any one of claims 1 to 7, characterized in that The material of the organic glue dots is selected from at least one of thermosetting resin, thermoplastic resin, rubber and elastomer.
9. The solar cell according to claim 8, characterized in that The thermosetting resin includes at least one of epoxy resin, phenolic resin, unsaturated polyester resin, polyurethane resin, silicone resin and polyimide resin; the thermoplastic resin includes at least one of polyethylene resin, polypropylene resin, polyvinyl chloride resin, polystyrene resin and acrylic resin; the rubber includes at least one of chloroprene rubber, butyl nitrile ethylene propylene rubber, fluororubber and polyisobutylene rubber; the elastomer includes polyurethane elastomer.
10. The solar cell according to any one of claims 1 to 7, characterized in that The metal layer and the conductive body are both made of copper.
11. A method for manufacturing a solar cell, characterized in that: include: forming a metal seed layer on a battery substrate; Applying a first photosensitive adhesive on the battery substrate to cover the metal seed layer, wherein the first photosensitive adhesive comprises a photosensitive material and an organic adhesive; Exposing and developing the first photosensitive resin to remove the photosensitive material in the first photosensitive resin, so that the organic adhesive forms discretely distributed organic glue dots on the metal seed layer, and the organic glue dots are at least distributed in the gate line area where the gate line is to be formed; The gate lines are formed in the gate line area by an electroplating process.
12. The method for manufacturing a solar cell according to claim 11, characterized in that: The step of exposing and developing the first photosensitive adhesive to remove the photosensitive material in the first photosensitive adhesive includes: Exposing the first photosensitive resin in the gate line area; Using a first alkaline solution to remove the first photosensitive resin outside the grid line area; The photosensitive material in the first photosensitive glue in the grid line region is removed by using a second alkaline solution, so that the organic adhesive forms the organic glue dots which are discretely distributed in the grid line region.
13. The method for manufacturing a solar cell according to claim 12, characterized in that: The first alkaline solution is a weak alkaline solution, and the second alkaline solution is a strong alkaline solution.
14. The method for manufacturing a solar cell according to claim 13, characterized in that: The first alkaline solution is a sodium carbonate solution, and the second alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.
15. The method for manufacturing a solar cell according to claim 12, characterized in that: The first photosensitive resin in the gate line area is exposed by a laser printing process.
16. The method for manufacturing a solar cell according to any one of claims 11 to 15, characterized in that: The organic adhesive is selected from at least one of a thermosetting resin, a thermoplastic resin, a rubber and an elastomer.
17. The method for manufacturing a solar cell according to claim 16, characterized in that: The thermosetting resin includes at least one of epoxy resin, phenolic resin, unsaturated polyester resin, polyurethane resin, silicone resin and polyimide resin; the thermoplastic resin includes at least one of polyethylene resin, polypropylene resin, polyvinyl chloride resin, polystyrene resin and acrylic resin; the rubber includes at least one of chloroprene rubber, butyl nitrile ethylene propylene rubber, fluororubber and polyisobutylene rubber; the elastomer includes polyurethane elastomer.
18. The method for manufacturing a solar cell according to any one of claims 11 to 15, characterized in that: The mass proportion of the organic adhesive in the first photosensitive adhesive is 0.001%~10.0%.
19. The method for manufacturing a solar cell according to any one of claims 11 to 15, characterized in that: The viscosity of the organic adhesive is 1000-5000 mPa·s.
20. The method for manufacturing a solar cell according to any one of claims 11 to 15, characterized in that: The thickness of the first photosensitive adhesive is 0.5-3 μm.
21. The method for manufacturing a solar cell according to any one of claims 11 to 15, characterized in that: The step of manufacturing the gate line in the gate line area by electroplating process comprises: Applying a second photosensitive adhesive on the battery substrate to cover the metal seed layer; Removing the second photosensitive resin in the gate line area by exposure and development; Placing the battery substrate in an electroplating solution for electroplating to form the grid lines in the grid line area; Using a third alkaline solution to remove the second photosensitive resin outside the grid line area; The metal seed layer outside the gate line region is removed using an acid solution.
22. The method for manufacturing a solar cell according to claim 21, characterized in that: After the step of forming the grid lines in the grid line area by electroplating, the method for forming the solar cell further comprises: The cell substrate with the grid lines is subjected to light injection treatment.
23. The method for manufacturing a solar cell according to claim 22, characterized in that: The light injection temperature of the light injection treatment is 200-220° C., and the light injection time is 60-120 seconds.
24. A photovoltaic module, characterized in that: A solar cell comprising the solar cell described in any one of claims 1 to 10, or a solar cell manufactured by the method for manufacturing a solar cell described in any one of claims 11 to 23.
Citation Information
Cited By
Solar cell and photovoltaic module
CN121152395A